Construct Validity of the EuroQoL–5 Dimension and the Health Utilities Index in Head and Neck Cancer. (May 2022) - Noel, Christopher W.; Keshavarzi, Sareh; Forner, David; Stephens, Robert F.; Watson, Erin; Monteiro, Eric; Hosni, Ali; Hansen, Aaron; Goldstein, David P.; de Almeida, John R.
Objective: The objective of this study was to evaluate the construct validity of 2 health utility instruments—the EuroQoL–5 Dimension (EQ-5D) and the Health Utilities Index–Mark 3 (HUI-3)—and to compare them with disease-specific measures in patients with head and neck cancer. Study Design: Prospective cross-sectional analysis. Setting: Princess Margaret Cancer Centre. Methods: Patients were administered the EQ-5D, HUI-3, the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire (EORTC QLQ-C30) and its head and neck cancer module (EORTC QLQ-H&N35), and the University of Washington Quality of Life Questionnaire (UWQoL). Several a priori expected relations were examined. The correlative and discriminative properties of the various instruments were examined. Results: A total of 209 patients completed the 4 questionnaires. A significant ceiling effect was observed among EQ-5D responses (23% reported a maximum score of 1). The EQ-5D (rho = 0.79) and HUI-3 (rho = 0.60) had a strong correlation with the social-emotional domain of the UWQoL. The EQ-5D had a moderate correlation with the physical domain of the UWQoL (rho = 0.42), whereas the HUI-3 had a weak correlation (rho = 0.29). The EQ-5D and HUI-3 were able to distinguish among levels of health severity measured on the EORTC QLQ-C30 though not the QLQ-H&N35. Comparatively, the UWQoL was able to distinguish levels of disease severity on the EORTC QLQ-C30 and QLQ-H&N35. Conclusion: The results of this study demonstrate that disease-specific domains from head and neck quality-of-life instruments are not strongly correlated with the EQ-5D and HUI-3. Consideration should be put toward development of a disease-specific preference-based measure for health economic evaluation. Level of evidence: 4.